FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MINUM OBAT ANTIRETROVIRAL DI KELOMPOK DUKUNGAN SEBAYA SEHATI MADIUN (FACTORS AFFECTING ADHERANCE OF TAKING ANTIRETROVIRAL DRUGS IN SEBAYA SEHATI GROUPS MADIUN) - Ratnawati, Riska (STIKes Maharani Malang, 2017)
Provision of antiretroviral therapy dramatically decrease the mortality and morbidity of people with HIV / AIDS. Antiretroviral therapy was reduced the rate of HIV transmission in the community, reduced morbidity and mortality associated with HIV, improved the quality of life of , restored and maintained immune function, suppressed viral replication maximally and on continuously. purpose of the research is for knowing was to determine the factors that influence adherence to the use of antiretroviral drugs in HIV / AIDS patients.The type of research is observational analytic with cross sectional approach. The sampling technique used was total sampling of 46 respondents. Data collection using questionnaire through interview. Data analysis was done bivariate and multivariate. The results showed that the factors that influence the adherence of taking ARV drugs among others. The results showed that factors affecting ARV drug adherence were ARV therapy guidelines (p = 0,000, OR = 24.0; 95% CI = 7,9-12,4), coexistent disease characteristics (p = 0.001; OR = 6.66, 95% CI = 1.6-22.2), and family support (p = 0.001; OR = 4.4; 95% CI = 1.3-12.4). This study demonstrates the importance of health counseling to improve adherence to antiretroviral drugs